2017
DOI: 10.3390/catal7050129
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Low-Temperature CO Oxidation over Mesoporous CuO-TiO2 Nanotube Catalysts

Abstract: Supported copper oxide nanoparticles have attracted considerable attention as active and non-precious catalysts for many catalytic oxidation reactions. Herein, mesoporous xCuO-TiO 2 nanotube catalysts were fabricated, and their activity and kinetics toward CO oxidation were studied. The morphology and structure of the prepared catalysts were systematically studied using SEM, TEM, EDS, EDX, XRD, TGA, BET, XPS, H 2 -TPR, and Raman techniques. The BET surface area study revealed the effect of the large surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 63 publications
5
33
0
Order By: Relevance
“…The former two peaks (144 and 394 cm −1 ) were attributed to the E g and B 1g O Ti O bending modes, respectively, and shifted to higher wavenumbers with increasing guest metal ions. The latter two were attributed to A 1g and E g Ti O stretching modes, respectively, and shifted to lower wavenumbers with increasing metal ions [10,15]. This indicates that the bending and stretching modes are oppositely affected by the loaded metal ions.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The former two peaks (144 and 394 cm −1 ) were attributed to the E g and B 1g O Ti O bending modes, respectively, and shifted to higher wavenumbers with increasing guest metal ions. The latter two were attributed to A 1g and E g Ti O stretching modes, respectively, and shifted to lower wavenumbers with increasing metal ions [10,15]. This indicates that the bending and stretching modes are oppositely affected by the loaded metal ions.…”
Section: Methodsmentioning
confidence: 90%
“…For thermal CO oxidation tests [7,14,15], Fang et al prepared CuO/TiO 2 catalysts using coprecipitation and impregnation methods and reported a CO oxidation onset at approximately 50 °C [14]. The high catalytic activity was attributed to the interfacial bond formation of hybrid Ti O Cu and the consequent stabilization of Cu + species.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies reported in the literature which explore the kinetics of CH 4 oxidation leading to power‐law and mechanistic investigations over various catalysts. The power‐law model is reported by limited investigators, whereas mechanistic models such as Langmuir‐Hinshelwood (LH), Eley‐Rideal (ER), and Mars van Krevelen (MvK) are widely investigated. Abbasi et al studied power‐law kinetics of CH 4 over thermally‐aged Pt and steam‐aged Pt‐Pd catalysts using the intergral method of analysis of kinetic data.…”
Section: Introductionmentioning
confidence: 99%
“…They reported the activation energy over the best Co 3 O 4 ‐O catalyst to be 42.3 kJ/mol. Zedan et al studied the kinetics of CO oxidation over the best catalyst composition (50 %CuO‐TiO 2 ) in the temperature range 60–85 °C and the conversion limit of 15 %. The authors reported the order and activation energy for CO oxidation as 0.91 and 81 kJ/mol, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) and nitrogen oxides (NO x ) generated from industrial production and human activities are hazardous gases that would cause severe air pollution. The nanocomposites such as mesoporous CuO-TiO nanotubes (Zedan et al [7]) and CuO nanorods-reduced graphene oxide (Wang et al [8]) were developed for catalytic oxidation of CO to CO 2 at low temperatures. Di and co-workers [9] discovered that the thermal activation atmosphere dramatically impacted the catalytic activity of CuBTC MOF for CO oxidation.…”
mentioning
confidence: 99%